2012
DOI: 10.4172/2161-0665.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Values in Children with Beta Thalassemia Major

Abstract: Objective: The purpose of the study was to examine the blood lipid profile in children with beta-Thalassemia major, and to determine the factors that affect it.Material and Method: Files of eighty-five patients between the ages of five and fifteen with beta-Thalassemia major who were receiving regular chelation therapy followed by from paediatric policlinic of our hospital were examined retrospectively. Blood lipid profiles of fifty-five healthy children were taken for use as the control group. A total of 117 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
4
9
1
3
Order By: Relevance
“…neither low nor high. Results of present study correlate well with previous study [14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…neither low nor high. Results of present study correlate well with previous study [14][15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…This alteration is likely due to diminished hepatic biosynthesis as of anemia and iron overload, while a reduced extra hepatic lipolytic activity could account for the rise in circulating TG [14] . Iron-loading and the effects of repeated blood transfusions induce a hepatic acute-phase response, which could determine an LDL-class shift towards protein-rich, denser particles [14,17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] But Infections such as HBV, HCV, and HIV can be observed through frequent transfusions in children with Beta Thalassemia major (BTM). [5] Various endocrine, cardiac, and hepatic diseases may occur depending, on excessive iron-loading. Failure of pubertal growth, delay or absence of sexual development, amenorrhea, sexual dysfunction and infertility due to hypogonadism are well recognized disturbances of the hypothalamic -pituitary -gonadal axis in Beta Thalassemia patients.…”
Section: Section: Paediatricsmentioning
confidence: 99%
“…Deficiency of zinc causes growth retardation, defective collagen synthesis, skeletal abnormalities, poor wound healing, impaired immune function, night blindness, sickle cell anemia and impaired protein synthesis (Gropper & Smith, ). Previous studies showed either lower (Arıca, Arıca, Özer, & Çevik, ; Keikhaei, Badavi, Pedram, Zandian, & Fakher Rahim, ; Mahyar et al, ) or higher concentrations of Zn in patients (Mehdizadeh, Zamani, & Tabatabaee, ), and also showed correlation with Cu (Bashir, ; Fukushima et al, ; Mahyar et al, ; Naji, ), which is an important constituent of hemoglobin. In this study, Cu levels were found to be higher in patients as compared with controls.…”
Section: Discussionmentioning
confidence: 97%